Mejora en el área técnica de la empresa de refrigeración y aire acondicionado Frio Group S.A.C. - Girao Quispe, Juan Manuel (2019)
The processes within organizations are fundamental for the proper functioning of all their areas. Developing them in an appropriate manner not only means maintaining order, but also having a better response time, being more productive and above all reducing cost overruns. Taking into consideration the previous premise and with the use of industrial engineering techniques, the presented theses is about the improvement of the technical area of the company Frio Group S.A.C.